The Role of the National and University Library of Slovenia in a Multinational Research Project (IMPACT): a Case Study - Vodopivec, Ines (LIBER Quarterly: The Journal of the Association of European Research Libraries, 2012)
In this paper, the participation and the role of individual libraries acting as partners in research project consortia, dealing with digitisation issues are analysed, following the example of the National and University Library of Slovenia (NUK) as a partner in the IMPACT project — Improving Access to Text. IMPACT is funded under the Seventh Framework Programme of the European Commission (FP7) aimed at improving automated text recognition of digitised materials from different European digital collections. To achieve the project’s objectives, a consortium of partners comprised of several European libraries, information technology and software engineering centres, and linguistic institutes was established. The consortium’s work was based on interdisciplinary collaboration in which libraries (like NUK) played an important role firstly as demonstrators of tools and procedures developed within the project, and secondly as representatives of end-users’ needs and demands. Different European digitisation projects in the past have already included national libraries as project partners and the results of collaboration have been so far quite positive. A case study methodology is used for exploring several dimensions of such collaboration. First of all, the study shows that the consortium ensures libraries the economic and expert groundwork needed for the effective realization of the objectives outlined in the framework of the project. Secondly, the study shows positive results when comparing the sum total of knowledge and experience gained over the course of the project and the efforts invested in it by individual libraries. On the basis of such a success, NUK will be able to expand its digitisation plans. Other advantages include more concrete project outcomes, such as the formation of a common multinational digital collection, applicable OCR technology and metadata standardisation. A comparative study with some of NUK’s other on-going projects shows differences and similarities in the library’s collaboration in applicative and research project schemes. Furthermore, the main results of the library as a demonstrator in the project are presented — they are in accordance with the library’s strategic goals and its official role in the information society. Thus, this case study may be considered as an example of a best practice for participation of a national library in interdisciplinary research projects. It also shows, that national libraries can be important and active partners not only in an applicative, but also in scientific research project consortia.